Leadership styles of futsal coaches from athletes' perceptions - Selcuk Bugdaycı; Ugur Abakay; Ozlem Zengın; Hayri Demır (Selcuk University, 2017)
The present is a descriptive research, the purpose of which is defining leadership styles of futsal coaches, who serve as faculty members at higher education institutions in Turkey, from athletes' perceptions. The data were collected from 337 athletes (147 female, 188 male), who participated in UNILIG futsal competitions organized by the Ministry of Youth and Sports. "Leadership Scale for Sports: Athlete's Perceptions of Coach's Behaviour" adapted to Turkish by Güngörmüş et al. was utilized as the data collection tool. According to the findings of the present research conducted to define the leadership styles of futsal coaches, futsal players' perceptions of their coaches' educative supportive and explanatory awarding behaviours are negative, perceptions of democratic and autocratic behaviours are positive, female players' perceptions of educative teaching, democratic behaviours and explanatory-awarding behaviours are more positive than male players, and perceptions of democratic behaviours of athletes, who have been training with the same coach for 5 years are more positive than the ones, who have been training with the same coach for 3 years or less.